A time–frequency analysis approach for condition monitoring of a wind turbine gearbox under varying load conditions. (December 2015) - Antoniadou, I.; Manson, G.; Staszewski, W.J.; Barszcz, T.; Worden, K.
Abstract: This paper deals with the condition monitoring of wind turbine gearboxes under varying operating conditions. Generally, gearbox systems include nonlinearities so a simplified nonlinear gear model is developed, on which the time–frequency analysis method proposed is first applied for the easiest understanding of the challenges faced. The effect of varying loads is examined in the simulations and later on in real wind turbine gearbox experimental data. The Empirical Mode Decomposition (EMD) method is used to decompose the vibration signals into meaningful signal components associated with specific frequency bands of the signal. The mode mixing problem of the EMD is examined in the simulation part and the results in that part of the paper suggest that further research might be of interest in condition monitoring terms. For the amplitude–frequency demodulation of the signal components produced, the Hilbert Transform (HT) is used as a standard method. In addition, the Teager–Kaiser energy operator (TKEO), combined with an energy separation algorithm, is a recent alternative method, the performance of which is tested in the paper too. The results show that the TKEO approach is a promising alternative to the HT, since it can improve the estimation of the instantaneous spectral characteristics of the vibration data under certain conditions. Abstract : Highlights: The effect of time varying loads of wind turbine gearboxes is examined. The study uses both simulated and real wind turbine gearbox data. The Teager Energy Operator is applied as an alternative AM–FM separation method. The mode mixing problem of the EMD is discussed.